2015
DOI: 10.2196/jmir.3812
|View full text |Cite
|
Sign up to set email alerts
|

Twitter Sentiment Predicts Affordable Care Act Marketplace Enrollment

Abstract: BackgroundTraditional metrics of the impact of the Affordable Care Act (ACA) and health insurance marketplaces in the United States include public opinion polls and marketplace enrollment, which are published with a lag of weeks to months. In this rapidly changing environment, a real-time barometer of public opinion with a mechanism to identify emerging issues would be valuable.ObjectiveWe sought to evaluate Twitter’s role as a real-time barometer of public sentiment on the ACA and to determine if Twitter sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“… 33 34 Researchers have also been experimenting with sentiment analysis of social media for healthcare research. 13 14 16 17 Sentiment can be determined in several ways, with the goal being to classify the underlying emotional information as either positive or negative. This can be done either purely by human input or by an algorithm trained to complete this process based on a human-classified set of objects, and reliability is largely a function of the method used.…”
Section: Introductionmentioning
confidence: 99%
“… 33 34 Researchers have also been experimenting with sentiment analysis of social media for healthcare research. 13 14 16 17 Sentiment can be determined in several ways, with the goal being to classify the underlying emotional information as either positive or negative. This can be done either purely by human input or by an algorithm trained to complete this process based on a human-classified set of objects, and reliability is largely a function of the method used.…”
Section: Introductionmentioning
confidence: 99%
“…Computerized content analysis utilizing techniques such as natural language processing (NPL) show great promise (Wong et al, 2015). However, these techniques focus on social media language in isolation of conversation.…”
Section: Analysis and Interpretationmentioning
confidence: 99%
“…One study of postings on a weight-loss blog suggested that sharing one’s negative emotions, as indicated by the use of sadness words, was linked to greater success in losing weight [ 5 ]. Similar explorations of social media as a way to understand health attitudes and behavior (eg, [ 6 - 8 ]) and track health outcomes (eg, [ 9 , 10 ]) further illustrate the potential in exploring social media data to establish their utility for policy uses.…”
Section: Introductionmentioning
confidence: 96%
“…Research on Twitter data suggests that sentiment (as indicated by word use) in tweets can be used to model life satisfaction [ 7 ], happiness [ 6 ], and heart disease mortality [ 10 ] and health. Sentiment revealed in social media data can also help predict engagement in healthy behaviors, such as health insurance enrollment [ 8 ].…”
Section: Introductionmentioning
confidence: 99%